The Higher Education Managerial Revolution?
XIII, 297 p.
Keywords: Hedda, founded on 1 January 2001, is a consortium of nine European centres and institutes devoted to research on higher education (see web site: www. uv. uio. nolhedda). Theconsortium·saims are to strengthen the relationship between higher education research and practice, organise and support available academic expertise, and further knowledge on higher education in Europe in such a way that it becomes more accessible and visible at the supranational and international levels. To contribute to the consortium's objectives CIPES, one of its member institutes, and Hedda have taken a new initiative in the field of research on higher education, that is, an annual seminar focused on one specific topic of research. The topic is determined by the Hedda Board from among the most burning issues of present day higher education policies. The tirst seminar was a four-day scientific event on Governance Structures in Higher Education Institutions. The seminar was held along the banks of the Douro River, Portugal, on 13-17 October 2001. The second seminar focused on the Emergence of Managerialism in Higher Education Institutions and took place at the same location on 4-9 October 2002. The theme of the third seminar is Markets in Higher Education to be held 2-6 October 2003. Participation in the seminars is limited to select Hedda researchers and invited researchers of international standing, all of whom are active in the research theme of each particular seminar.